Developmentally‐Inspired Shrink‐Wrap Polymers for Mechanical Induction of Tissue Differentiation. (18th February 2014) - Hashmi, Basma; Zarzar, Lauren D.; Mammoto, Tadanori; Mammoto, Akiko; Jiang, Amanda; Aizenberg, Joanna; Ingber, Donald E.
<x xml:space="preserve">Abstract</x> A biologically inspired thermoresponsive polymer has been developed that mechanically induces tooth differentiation in vitro and in vivo by promoting mesenchymal cell compaction as seen in each pore of the scaffold. This normally occurs during the physiological mesenchymal condensation response that triggers tooth formation in the embryo. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>